A Tale of Cyclicality, Aid Flows and Debt: Government Spending in Sub-Saharan Africa - (:unkn) unknown (My University, 2011)
This paper documents cyclical patterns of government expenditures in Sub-Saharan Africa since 1970 and explains variation between countries and over time. Controlling for endogeneity and applying dynamic generalised method of moment (GMM) techniques, it finds that government expenditures are slightly more procyclical in Sub-Saharan Africa than in other developing countries and some evidence that procyclicality in Africa has declined in recent years after a period of high procyclicality during the 1980s and 1990s. We find suggestive evidence that greater fiscal space, proxied by lower external debt, and better access to concessional financing, proxied by larger aid flows, contributed to diminishing procyclicality in the region. We do not find, however, any evidence that political institutions affect fiscal procyclicality in Sub-Saharan Africa.
Keywords: African Research